Genome-wide analysis of changes in miRNA and target gene expression reveals key roles in heterosis for Chinese cabbage biomass. (1st March 2021) - Li, Peirong; Su, Tongbing; Zhang, Deshuang; Wang, Weihong; Xin, Xiaoyun; Yu, Yangjun; Zhao, Xiuyun; Yu, Shuancang; Zhang, Fenglan
Abstract: Heterosis is a complex phenomenon in which hybrids show better phenotypic characteristics than their parents do. Chinese cabbage ( Brassica rapa L. spp. pekinensis ) is a popular leafy crop species, hybrids of which are widely used in commercial production; however, the molecular basis of heterosis for biomass of Chinese cabbage is poorly understood. We characterized heterosis in a Chinese cabbage F1 hybrid cultivar and its parental lines from the seedling stage to the heading stage; marked heterosis of leaf weight and biomass yield were observed. Small RNA sequencing revealed 63 and 50 differentially expressed microRNAs (DEMs) at the seedling and early-heading stages, respectively. The expression levels of the majority of miRNA clusters in the F1 hybrid were lower than the mid-parent values (MPVs). Using degradome sequencing, we identified 1, 819 miRNA target genes. Gene ontology (GO) analyses demonstrated that the target genes of the MPV-DEMs and low parental expression level dominance (ELD) miRNAs were significantly enriched in leaf morphogenesis, leaf development, and leaf shaping. Transcriptome analysis revealed that the expression levels of photosynthesis and chlorophyll synthesis-related MPV-DEGs (differentially expressed genes) were significantly different in the F1 hybrid compared to the parental lines, resulting in increased photosynthesis capacity and chlorophyll content in the former. Furthermore, expression of genes known to regulate leaf development was also observed at the seedling stage. Arabidopsis plants overexpressing BrGRF4.2 and bra-miR396 presented increased and decreased leaf sizes, respectively. These results provide new insight into the regulation of target genes and miRNA expression patterns in leaf size and heterosis for biomass of B. rapa .